Ответ:
Пошаговое объяснение:
а ) y = 7²ˣ ; y' = 7²ˣ ln7 ( 2x )' = 7²ˣ ( 2ln7 ) ;
б ) y = ln√( 2x - 1 ) = 1/2 ln( 2x - 1 ) ; y' = 1/2 * 1/( 2x - 1 ) * ( 2x - 1 )' =
= 2/[ 2( 2x - 1 ) ] = 1/( 2x - 1 ) ;
в ) y = sin5x ( 1 + 2cos3x ) ; y' = ( sin5x )' ( 1 + 2cos3x ) + sin5x ( 1 + 2cos3x )' =
= 5cos5x (1 + 2cos3x ) + sin5x (0 - 2*3sin3x )= 5cos5x ( 1 + 2cos3x ) - 6sin3xsin5x .
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
а ) y = 7²ˣ ; y' = 7²ˣ ln7 ( 2x )' = 7²ˣ ( 2ln7 ) ;
б ) y = ln√( 2x - 1 ) = 1/2 ln( 2x - 1 ) ; y' = 1/2 * 1/( 2x - 1 ) * ( 2x - 1 )' =
= 2/[ 2( 2x - 1 ) ] = 1/( 2x - 1 ) ;
в ) y = sin5x ( 1 + 2cos3x ) ; y' = ( sin5x )' ( 1 + 2cos3x ) + sin5x ( 1 + 2cos3x )' =
= 5cos5x (1 + 2cos3x ) + sin5x (0 - 2*3sin3x )= 5cos5x ( 1 + 2cos3x ) - 6sin3xsin5x .